Assessing public park tree canopy diversity in Fort Collins, CO - Gutru, Jake, author; Mola, John, advisor; Hart, Sarah, committee member (Colorado State University. Libraries, 2025)
The urban canopy of Fort Collins provides tens of thousands of dollars to the city in the form of decreased heating/cooling costs, reduced stormwater runoff, and increased property value for residents. To preserve these benefits, these trees should be managed with diversity and potential disturbances in mind. Specifically, public parks should be closely examined as they are areas of high recreational traffic, which could mean diseases are more likely to be introduced here. This paper describes how publicly available data was used to examine the tree species diversity and adherence to the 10/20/30 rule for 53 public parks across Fort Collins. Despite Fort Collins' assessment of the state of their urban canopy in their Urban Forest Strategic Plan, only 2 of the 53 parks adhere to the 10/20/30 rule. Parks which are particularly diverse or non-diverse for their size are highlighted, and potential actions that the town can take to manage these parks are suggested based on these findings.
Keywords: urban; forestry; diversity; disease